A code division multiplexing scheme for satellite digital audio broadcasting. - Weerackody, V. (IEEE Journal on selected areas in communications)
Several systems are being considered for digital audio broadcasting (DAB) and some of these systems will be deployed for commercial use. In this paper, we consider a code division multiplex (CDM) scheme for satellite DAB. For diversity purposes, this system makes use of at least two satellites, and in urban areas, where the satellite signals are shadowed by large structures, a terrestrial network is employed. We present a forward error protection (FEC) scheme that is robust under a variety of channel conditions, especially in cases where the received signal is severely attenuated because of highway underpasses and tunnels. This FEC scheme makes use of time diversity, and this introduces a large delay. Such delays will not affect the performance of broadcast systems; however, the delay will be an issue during tuning when a switch to another channel occurs. We introduce a separate low-delay low-rate tuning channel to facilitate tuning. Extensive simulation results are given to examine the performance of the system, and it is shown that about 70 audio channels, each with a rate of 96 kbit/s, can be satisfactorily supported in a bandwidth of approximately 12.5 MHz in most of the channel conditions considered